Peningkatan Wawasan Kader Puskesmas dalam Deteksi Resiko Stunting di Wilayah Kerja Puskesmas Lubuk Buaya - Deswita Deswita; Ira Mulya Sari; Arif Rohman Mansur; Lili Fajria; Yelly Herien; Hermalinda Hermalinda (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2019)
The Lubuk Buaya Health Center has the highest number of children under five in the city of Padang. It has the most stunting cases in the city of Padang. The partner in IbDM is a group of cadres from the village of Pasie Nan Tigo. The formulated problems of partners are the low knowledge and skills of cadres in early detection of the risk of stunting in children. The objective is to increase the understanding of management, cadre knowledge and expertise in the implementation of nutrition services and counselling inside and outside integrated health post and in-home visits. The method used is health education and cadre training by providing pretest and posttest. Knowledge questionnaires on stunting prevention and detection were given to cadres before and after training. The results of this training found that cadre's average knowledge increased after being given training. This training can increase the knowledge of cadres regarding early detection of the risk of stunting in children. It is expected that cadres can develop the ability to detect the risk of stunting in early childhood cadres so that they are able to provide counselling to all families who have children when visiting the integrated health post.